Identifikasi struktur bawah permukaan tanah menggunakan metode geolistrik konfigurasi Wenner-Schlumberger di Kabupaten Rokan Hulu - Lihayati, Rifa; Septania, Nadia Luanda; Haroky, Faruq (Universitas Tangerang Raya, 2024)
This study aims to determine the subsurface structure using the geoelectric configuration method Wenner-Schlumberger in the geothermal area of Pawan Village. Data retrieval were carried out in 4 paths with different lengths of each track. Line 1 is located at 00°49'31.49